Building a Multidisciplinary Academic Surgical Gender-affirmation Program: Lessons Learned - Manrique, Oscar J. (Plast Reconstr Surg Glob Open, 2021)
BACKGROUND: Every day, we see more patients present to hospitals and clinics seeking gender-affirmation care to ameliorate the symptoms of gender dysphoria. However, to provide a multidisciplinary approach, it is important to offer an integrated clinical program that provides mental health assessment, endocrine therapy, physical therapy, research, and the full spectrum of surgical services devoted to transgender patients. This article describes our experience on building a specialized, multidisciplinary, academic state-of-the-art gender-affirmation program. METHODS: Herein, we describe the main and critical components on how to build a multidisciplinary academic gender-affirmation program. We share our lessons learned from this experience and describe how to overcome some of the obstacles during the process. RESULTS: Building a multidisciplinary academic gender-affirmation program requires an invested team, as each and every member is essential for feedback, referrals, and to improve patient’s experience. Institutional support is essential and by far the most important component to overcome some of the obstacles during the process. Having all team members working under the same institution provides all the critical components needed to improve outcomes and patient satisfaction. In addition, the collection of prospective data with a well-structured research team will provide information needed to improve clinical services and standardize clinical protocols, while leaving space for innovation. CONCLUSIONS: This article describes the steps and experience needed to build a multidisciplinary holistic academic gender-affirmation program. We provide our lessons learned during the process that will help guide those who intend to start an academic gender-affirmation program.